2008
DOI: 10.1007/bf03017204
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management of pregnant women with sickle cell disease — effect on postnatal sickling complications

Abstract: Purpose: Currently, there is no consensus regarding the choice of anesthetic technique for parturients with sickle cell disease (SCD). The aim of the study was to determine the impact of the anesthetic technique on the occurrence of postnatal sickling complications. Methods:We reviewed the charts of all pregnant women with SCD who had given birth in our institution between January 2002 and January 2007. Data related to pregnancy and anesthetic management and complications related, or unrelated, to SCD were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…GA was identified as a risk factor for maternal complications in women with SCA. Camous et al [ 3 ] considered GA to be a risk factor for postnatal sickling (acute chest syndrome, vaso-occlusive crisis, and stroke). However, neuraxial anesthesia was not identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GA was identified as a risk factor for maternal complications in women with SCA. Camous et al [ 3 ] considered GA to be a risk factor for postnatal sickling (acute chest syndrome, vaso-occlusive crisis, and stroke). However, neuraxial anesthesia was not identified.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, adequate hydration before spinal anesthesia, uterine displacement, and prompt diagnosis and treatment of hypotension with fluid boluses and ephedrine are important measures to minimize the duration and occurrence of hypotension. Interestingly, despite the vasoconstriction caused by ephedrine, which is critical for patients with SCA, Camous et al [ 3 ] found that ephedrine was not a risk factor for postnatal sickling complications in parturients with SCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative hemodynamics was maintained to avoid hypotension and tachycardia. Intraoperative ABG showed pH at 7.409, pCO 2 -30.6, pO 2 -91.1, HCO 3 -20.7, and saturation at 99.1%.…”
Section: Case Reportmentioning
confidence: 96%
“…Since ACS may occur as a postoperative complication in patients with SCD, especially following abdominal surgery (4,14), vaginal delivery is preferred over Caesarean delivery when possible.…”
Section: Casementioning
confidence: 99%